Forest landscape restoration in Ethiopia: Progress and challenges - Kassa, Habtemariam; Abiyu, Abrham; Hagazi, Niguse; Mokria, Mulugeta; Kassawmar, Tibebu; Gitz, Vincent (Frontiers in Forests and Global Change, 2022)
Ethiopia is committed to build a carbon neutral economy by 2030 as stated in its Climate Resilient Green Economy Strategy issued in 2011. Accordingly, in 2016 the country committed itself to restore 15 million hectares of degraded landscapes as part of the African Forest Landscape Restoration Initiative (AFR 100). Three major Forest Landscape Restoration (FLR) governance features have become clear to achieve this target. These are Participatory Forest Management (PFM) to engage communities in sustainably managing natural forests; Area Exclosure (AE) to socially fence hillsides and degraded communal lands and allow the areas to rest; and Sustainable Land Management (SLM) program that aims at conserving soil and water resources and planting trees to increase the national tree cover. After briefly describing the three major FLR governance features in Ethiopia, the authors briefly looked at the impacts of these FLR initiatives in terms of conservation and livelihood outcomes and further investigated them against the six principles of FLR by selecting few nationally relevant criteria under each principle. The paper concludes by identifying the limitations of these initiatives and suggests measures that need to be taken to sustainably improve the conservation and livelihood outcomes of FLR and if Ethiopia is to accomplish its AFR 100 commitment. It is hoped that the Ethiopian experience will inform policy makers and FLR practitioners in other countries.